Lucha agraria y revolución en el oriente de Durango (1900-1929) - Salmerón Sanginés, Pedro (El Colegio de México, A.C., 2006)
This paper seeks to show the continuity of land struggles in the old Cuencame district in Eastern Durango during the first decades of the twentieth century and to explain why this region became a highly potential revolutionary center. It also seeks to understand the regional revolutionary process and the forms it took up during different  moments of the land conflict. Finally, it rescues the figures of two peasant caudillos, Calixto Contreras and Severino Ceniceros.